2012
DOI: 10.1186/1472-6882-12-215
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and phytochemical properties of Carpobrotus edulis (L.) bolus leaf used for the management of common infections in HIV/AIDS patients in Eastern Cape Province

Abstract: BackgroundCarpobrotus edulis (Mesembryanthemaceae), also known as igcukuma in Xhosa language is a medicinal plant used by the traditional healers to treat common infections in HIV/AIDS patients. Based on this information, we researched on the plant phytoconstituents, as well as its inhibitory effect using aqueous and three different organic solvent extracts in order to justify its therapeutic usage.MethodsAntioxidant activity of the extracts were investigated spectrophotometrically against 1,1- diphenyl-2-picr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 31 publications
10
72
1
Order By: Relevance
“…The results suggest that A. cobbe leaf extract might serve as a potent therapeutic agent for scavenging of free radicals and the regulation of pathological conditions caused by oxidative stress. The observed antioxidant effect of the plant extract could be attributed to the presence of polyphenolic compounds (Omoruyi et al, 2012). The results are in line with the previous studies which reported that the free radical scavenging activity of plant extracts correlate with the phenolic content (Omoruyi et al, 2012;Jain et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…The results suggest that A. cobbe leaf extract might serve as a potent therapeutic agent for scavenging of free radicals and the regulation of pathological conditions caused by oxidative stress. The observed antioxidant effect of the plant extract could be attributed to the presence of polyphenolic compounds (Omoruyi et al, 2012). The results are in line with the previous studies which reported that the free radical scavenging activity of plant extracts correlate with the phenolic content (Omoruyi et al, 2012;Jain et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…At the concentration 0.05 there is no significant different between the aqueous extract and the standard (P> 0.05). The IC50 value of the acetone leaf extract (0.13, 61.7%) is significantly higher than that of standard (vitamin C 0.30, 74.3%) the result is in agreement with Omoruyi et al (2012), who reported that IC50 values of methanol plant extract is significantly higher than that of BHT and Rutin. It was also revealed that the leaf extracts contain antioxidant properties than the bark extracts as shown in Table 2; this implies that most bioactive compound are stored on the trichomes which might probably be on the leaves as reported by Afolayan and Meyer (1997).…”
Section: Abts Radical -Scavenging Activitysupporting
confidence: 82%
“…However, there is no significance difference in the percentage inhibition of vitamin C and the acetone extract. The minimum inhibitory concentration obtained to reduce the nitric oxide radicals by 50% of the extracts of the leaves and bark of C. anisata is in the following order: acetone bark > dichloromethane bark > aqueous leaf > dichloromethane leaf > aqueous bark, it can be deduced that organic solvent processes strong antioxidant activity, this study is in agreement with other researchers investigating scavenging activity of nitric oxide (Omoruyi et al, 2012, Otang et al, 2012). This will contribute to scientific knowledge and could be a lead to potent herbal drug to the ailments and diseases associated to oxidative stress.…”
Section: Nitric Oxide Scavenging Activitysupporting
confidence: 81%
See 2 more Smart Citations